2009
DOI: 10.1016/j.jsat.2008.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Continuing care research: What we have learned and where we are going

Abstract: In the field of addiction treatment, the term “continuing care” has been used to indicate the stage of treatment that follows an initial episode of more intensive care. This article reviews controlled studies of continuing care conducted over the prior 20 years. The results indicate that continuing care interventions were more likely to produce positive treatment effects when they had a longer planned duration, made more active efforts to deliver treatment to patients, and were studied more recently. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
210
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 211 publications
(218 citation statements)
references
References 68 publications
7
210
0
1
Order By: Relevance
“…By specifi cally including the outcome of a lower likelihood of relapse to DWI, our fi ndings extend those of other studies in which more alcohol-related specialty care (McKay, 2009;Moos et al, 1999;Ritsher et al, 2002) and AA participation (Kaskutas et al, 2008;Timko and DeBenedetti, 2007) were associated with better drinking outcomes (e.g., abstinence) in general. They concur with conceptual models hypothesizing that a longer duration of help may reduce the risk of impaired driving among individuals prone to drive while intoxicated (Mann et al, 1983;Wells-Parker and Williams, 2002).…”
Section: Treatment Aa and Dwisupporting
confidence: 82%
See 1 more Smart Citation
“…By specifi cally including the outcome of a lower likelihood of relapse to DWI, our fi ndings extend those of other studies in which more alcohol-related specialty care (McKay, 2009;Moos et al, 1999;Ritsher et al, 2002) and AA participation (Kaskutas et al, 2008;Timko and DeBenedetti, 2007) were associated with better drinking outcomes (e.g., abstinence) in general. They concur with conceptual models hypothesizing that a longer duration of help may reduce the risk of impaired driving among individuals prone to drive while intoxicated (Mann et al, 1983;Wells-Parker and Williams, 2002).…”
Section: Treatment Aa and Dwisupporting
confidence: 82%
“…For example, the frequency with which individuals engage in DWI may moderate the effects of the amount and intensity of treatment or AA on subsequent drinking and driving behaviors. Generally, individuals with highly chronic and severe substance use problems have better outcomes when they receive more (and more intensive) treatment, whereas individuals with milder problems tend to improve whether they receive lower or higher amounts and intensities of help (Blonigen et al, 2009;Chen et al, 2006;McKay, 2009). Accordingly, future research should recognize that treatment and AA participation, whether mandated or voluntary, may not be suffi cient for some people who repeatedly engage in DWI to desist such behavior (DeYoung, 1997).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…[37][38][39] Substance use disorders are typically chronic disorders treated with acute care, yet they warrant flexible, patient-centered, longitudinal care. 40 There is an unmet need for treatment of substance use disorders; one study indicated that less than 10% of PSUDs were receiving treatment. 41 Among persons living with HIV who also have substance use disorders, access to substance use disorder treatment may also be limited or nonexistent.…”
mentioning
confidence: 99%
“…However, the addiction field has focused mainly on aftercare services involving 12-step participation or modalities conducted through specialty substance abuse treatment programs. Many of these increase the benefit of treatment (39), but in most cases the aftercare period is limited. At some point it ends, and patients become disconnected from the clinic, specialty care providers, and other resources and services (10).…”
mentioning
confidence: 99%